2017
DOI: 10.1016/j.cegh.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of communication disorders in a rural population at taluq level of Gujarat, India

Abstract: c l i n i c a l e p i d e m i o l o g y a n d g l o b a l h e a l t h 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…In the present study, out of 216 children who underwent cochlear implantation at various hospitals of the region under the School Health Program, 61% (132) were boys and 39% (84) were girls and there was significant difference across gender. This result is in coherence with the study by Sinha et al 14 where the prevalence of otological conditions was relatively higher in males (1.66%) than compared to females (1.63%) in the state of Gujarat. Similarly, the study by Patel et al 15 reported a total of 246 hearing-impaired children with a male: female ratio of 1.7:1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, out of 216 children who underwent cochlear implantation at various hospitals of the region under the School Health Program, 61% (132) were boys and 39% (84) were girls and there was significant difference across gender. This result is in coherence with the study by Sinha et al 14 where the prevalence of otological conditions was relatively higher in males (1.66%) than compared to females (1.63%) in the state of Gujarat. Similarly, the study by Patel et al 15 reported a total of 246 hearing-impaired children with a male: female ratio of 1.7:1.…”
Section: Discussionsupporting
confidence: 92%
“…13 One such scheme, School Health Program, has been running in the state of Gujarat where the overall prevalence of communication disorder is 4.09% with otological disorders ranked highest (3.30%). 14 The average age of suspicion about hearing loss in the state is reported to be 2.9 ± 1.7 years, with the first consultation done at 3.5 ± 1.5 years and the age of intervention performed at 7.8 ± 3.3 years. 15 Therefore, under School Health programme, the state government has been attempting to intervene individuals with profound hearing loss with free cochlear implantation and rehabilitation at various government hospitals since 2013.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few area specific prevalence studies carried out within India. [8][9][10][11][12][13][14] These studies report a high proportion of communication disorders in India when compared to the world population. Also, one can notice the difference in the proportion of the population affected per area.…”
Section: Introductionmentioning
confidence: 99%
“…A higher prevalence of ear-related than speech and language related communication disorders was found. Mishra et al 6 on the other hand, reported a much higher prevalence (15.14%) of communication disorders in the rural areas of Lucknow district. A study conducted by Das et al 7 in the rural areas of Kolkata district, reported a high prevalence of stroke leading to communication impairments.…”
Section: Introductionmentioning
confidence: 93%
“…A small number of area-specific prevalence studies are previously conducted within India. [5][6][7][8][9][10][11] These indicate a difference in the proportion of the population affected per area. A survey conducted by Sinha et al 5 in the rural population of Gujarat reported an overall 4.09% prevalence of communication disorders.…”
Section: Introductionmentioning
confidence: 99%